1997
DOI: 10.1111/j.1432-1033.1997.00561.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Properties of Acetyl‐CoA Synthetase (ADP‐forming), an Archaeal Enzyme of Acetate Formation and ATP Synthesis, from the Hyperthermophile Pyrococcus furiosus

Abstract: Acetyl-CoA synthetase (ADP-forming) is an enzyme in Archaea that catalyzes the formation of acetate from acetyl-CoA and couples this reaction with the synthesis of ATP from ADP and P, (acetyl-CoA + ADP + P, -acetate + ATP + CoA) [Schafer, T., Selig, M. & Schonheit, P. (1993) Arch. Microbiol. 159, 72-83]. The enzyme from the anaerobic hyperthermophile Pyrococcus furiosus was purified 96-fold with a yield of 20% to apparent electrophoretic homogeneity. The oxygen-stable enzyme had an apparent molecular mass of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 55 publications
4
75
0
Order By: Relevance
“…Whatever the role of the N-terminal domain may be, it is likely to also play a role in sensing acetyl-CoA. This conclusion was drawn on the basis of results from isothermal calorimetry experiments, which showed that SePat binds two molecules of acetyl-CoA: one binds to the N-terminal domain, and the other one binds to the catalytic domain (70,(72)(73)(74)(75)(76)(77).…”
Section: Bacterial Gcn5-related N-acyltransferasesmentioning
confidence: 98%
See 1 more Smart Citation
“…Whatever the role of the N-terminal domain may be, it is likely to also play a role in sensing acetyl-CoA. This conclusion was drawn on the basis of results from isothermal calorimetry experiments, which showed that SePat binds two molecules of acetyl-CoA: one binds to the N-terminal domain, and the other one binds to the catalytic domain (70,(72)(73)(74)(75)(76)(77).…”
Section: Bacterial Gcn5-related N-acyltransferasesmentioning
confidence: 98%
“…ADP-forming acyl-CoA synthetases have been characterized in archaea and protists (75)(76)(77). In spite of this homology, no catalytic activity has been attributed to the N-terminal domain of type I or type II GNATs (73,74).…”
Section: Bacterial Gcn5-related N-acyltransferasesmentioning
confidence: 99%
“…The genomes all possessed the ADP-forming subunit of acetyl-CoA synthetase that has been seen to catalyze acetate production in Pyrococcus furiosus and other archaea (Glasemacher et al, 1997). The presence of this enzyme suggests that acetyl-CoA could be converted to acetate; however genes for ethanol fermentation did not appear to be present.…”
Section: Smtz-1 Bin 83mentioning
confidence: 99%
“…ACD and SCS enzymes are able to bind and convert all purine nucleotides at site II, but some enzymes exhibit specificity for either the Ado or Guo nucleotide (2,21,24,38,40). Kinetic characterization of ckcACD1 revealed that both nucleotides are accepted as substrates (SI Appendix, Fig.…”
Section: Ckcacd1 and Ecscs Display Very Similar Features For The Catamentioning
confidence: 99%
“…ACDs have been studied in detail in hyperthermophilic archaea, where they function as the major energy-conserving enzymes in the course of anaerobic sugar and peptide fermentation (1)(2)(3)(4). It is believed that ACDs represent a primordial mechanism of ATP synthesis in the early evolution of life.…”
mentioning
confidence: 99%